Studi Deskriptif: Pengetahuan Anemia pada Remaja Putri Pesantren di Kota Tarakan - Dinda Safitri; Andi Yuniarsy Hartika; Donny Tri Wahyudi; Rahma Yulis (Pusat riset dan Inovasi Nasional, 2025)
Anemia is a global health problem that frequently affects adolescent girls, particularly in developing countries such as Indonesia. Adolescent girls are at a higher risk of anemia due to menstrual blood loss and inadequate nutritional intake. This study aims to describe the level of knowledge about anemia among female students in Islamic boarding schools in Tarakan City. The research employed a quantitative approach with a descriptive method. The sample consisted of 124 adolescent girls selected using a total sampling technique. Data were collected using a questionnaire adapted from the Guidelines for Assessing Nutrition-related Knowledge, Attitudes, and Practices (FAO) and De et al., comprising 11 statement items. The results showed that 39.5% of respondents had good knowledge, 34.7% had moderate knowledge, and 25.8% had poor knowledge, with a mean score of 70.24, standard deviation of 19.10, minimum score of 18.18, and maximum score of 100.00. The study concludes that most adolescent girls in Islamic boarding schools in Tarakan City have good knowledge about anemia, although continuous nutrition education remains necessary.